Temporal pattern of conduction recurrence during radiofrequency ablation for typical atrial flutter - Šťovíček, Petr; Fikar, Miroslav; Wichterle, Dan (Journal of cardiovascular electrophysiology, 2006)
INTRODUCTION: Conduction recurrence during radiofrequency (RF) ablation of cavotricuspid isthmus for typical atrial flutter is common. Understanding the temporal pattern of recurrences could help to predict a durable bidirectional block (BDB) and optimize the procedure. METHODS AND RESULTS: We analyzed atrial flutter ablations in 108 consecutive patients (85 males, age 63 +/- 11 years). RF energy was delivered through 8-mm tip or 4-mm cooled-tip catheter. On average, 18 +/- 11 pulses were necessary to achieve BDB. The time to recurrence of conduction after RF cessation was recorded. Early and late conduction recurrences were defined as < or =10 minutes and >10 minutes, respectively. Patients were observed for > or =30 minutes after bidirectional cavotricuspid isthmus (CTI) block was achieved. Conduction did not recur in 46 patients. In 8 cases, no block was achieved. A total of 167 conduction recurrences were recorded in the remaining 54 cases (1-10 per case). Of these, in 53 patients, recurrences were classified as early (98%) and 14 patients had late recurrences (8%). Thirteen patients had both early and late recurrences (24%). All but one late recurrence were preceded by at least one early recurrence. Absence of early recurrence had negative predictive value of 98%, while any early recurrence had positive predictive value of 26% for subsequent late conduction recovery. CONCLUSION: Incidence of isthmus conduction recurrence rapidly decayed during the waiting period. Absence of conduction recurrence within 10 minutes after first successful RF delivery was highly predictive of persistent BDB.
Keywords: retrospektivní studie; Humans; lidé středního věku; Middle Aged; Financing, Organized; Time Factors; financování organizované; mužské pohlaví; katetrizační ablace; Heart Conduction System; časové faktory; Atrial Flutter; ženské pohlaví; Catheter Ablation; flutter síní; lidé; Male; Retrospective Studies; převodní systém srdeční; Female